Evaluation of In Vitro Antioxidant and Pharmacological Activities of Carica papaya (Red Lady) Leaf Extracts with Physiological Relevance: Therapeutic Applications - Asadullah, Asadullah; Ahmed, Asif; Javaid Sidhu, Muhammad Jabran; Shahzad, Sana; Khalid, Naima; Arshad, Anam (Journal of Neonatal Surgery, 2025)
Background: Medicinal plants surge from traditional use, particularly in developing countries, and their antioxidant potential as natural pharmaceutical-alternatives and health-enhancing diets. Papaya, is known for its edible fruits and medicinal properties, with its leaves, especially the Red Lady (RL) variety, being highly therapeutic. Objective: This study compares the antioxidant activity of acetone and n-hexane extracts from Carica papaya leaves (RL). Methods: This experimental study was conducted at the Department of Pharmacology and Therapeutics at Baqai Medical College/University of Karachi, utilizing in-vitro techniques, spanned duration of 6months. The protocol entails preparing pure samples at 0.5mM in DMSO and crude samples at 0.5mg/ml in DMSO. A 0.3mM DPPH solution in ethanol is prepared using DPPH. The test involves mixing 95µl of the 300µM DPPH solution with 5µl of the 500µM test solution and incubating the mixture for 30minutes at 37ºC. Absorbance is measured at 517nm using a Spectra-Max-340-multi-plate-reader. During the reaction, the solution changes color from violet to pale-yellow, indicating reduction. Results: Acetone extract exhibited modest activity with 52.8%, 53.1% and 53.8% inhibition, but the n-hexane extract illustrate no activity, representing -8.5%, -9.0% and 9.2% -Inhibitions, while, Gallic Acid showed significant inhibition, reaching 95.0%, 95.3% and 95.6% at a concentration of 0.5mg/ml. Moreover, the acetone extract achieved from the Carica Papaya Leaves (RL) determined an IC50±SEM value of 476.4±0.51µg/mL, whereas gallic acid showed an IC50 value of 3.69µg/mL (p < 0.001). Conclusion: These results propose that the acetone extract from the Carica Papaya Leaves (RL) might possess certain anti-oxidant activity, whereas it is less potent than the standard drug